Implementation of Management Based School in Improving The Quality Of Secondary Education - Istijarti, Atiek; Riyanto, Yatim; Setyowati, Sri (International Journal for Educational and Vocational Studies, 2019)
The implementation of school-based management in Indonesia itself is contained in the Act National Education System Number 20 of 2003 which reads "management of education units early childhood, basic education and secondary education are implemented based on standards minimal service with the principle of school-based management. education Department National Republic of Indonesia calls SBM with School-Based Quality Improvement Management which is defined as "a management model that gives school more autonomy and encourage participatory decision making that directly involves school members to improve the quality of schools based on national education policies.